Halicephalobus gingivalis: A Rare Cause of Fatal Meningoencephalomyelitis in Humans - Papadi, Bhavesh (The American Society of Tropical Medicine and Hygiene, 2013)
The genus Halicephalobus consists of eight species of free-living nematodes. Only one species (H. gingivalis) has been reported to infect vertebrates. Human infection is extremely rare, and only four cases have been reported in the literature. These nematodes seem to exhibit neurotropism, but their life cycle, mode of infection, and risk factors are poorly understood. Neurohelminthiases are not commonly recognized in the United States and when they do occur, pose great diagnostic challenges because of lack of appropriate non-invasive screening and/or confirmatory tests. We report a challenging case of meningoencephalomyelitis caused by a Halicephalobus sp., in which the patient had a rapidly deteriorating clinical course. The case did not raise any clinical suspicion of neurohelminthiases, although increased eosinophils were present in the cerebrospinal fluid. This case presents an opportunity to highlight the importance of considering parasitic infection in meningoencephalitis or meningoencephalomyelitis presenting atypically.